Evaluation of the morpho-functional characteristics of the foot and the habit of walking barefoot in individuals with foot alterations - Carrasco, Aline Cristina; Bim, Cintia Raquel; Lucas, Wesley Tiemme; Silva, Mariana Felipe (O Mundo da Saúde, 2023)
This study aimed to evaluate the functional profile, foot characteristics, and barefoot walking habits of individuals with musculoskeletal foot alterations and compare them with control individuals. Participants were assessed through an electronic questionnaire. Anthropometric data, foot functionality, barefoot walking habits, footwear type, foot type, foot arch, stride type, and foot impairments were collected. The total sample consisted of 160 individuals divided into a control group (CG) (n=82) and a foot problems group (FPG) (n=78). Hallux valgus was the main foot problem in the FPG (24.4%), with a higher percentage of participants having chronic conditions (35.9%), cavus foot types (left foot (LF) 16.7% and right foot (RF) 19.2%), or flat foot types (LF 21.8% and RF 21.8%), and with a compromised Foot Function Index in 7% (P=0.001). Both groups considered barefoot walking healthy (72% CG and 66.7% FPG), but they are not practitioners of this habit (93.9% CG and 91% FPG). Shoes were the least utilized type of footwear in the FPG (10.3%). In conclusion, individuals in the FPG showed a stronger association between morpho-functional alterations and foot disorders. Although barefoot walking is considered beneficial for foot health in both groups, neither group practices this habit.